Photochromic core-shell structure organic metal silicon nano composite material as well as preparation and application thereof
By preparing a core-shell structured organometallic silicon nanocomposite material Pt-SiO2@SP-SiO2, the security and reversibility issues of existing dynamic optical encryption technologies have been solved. It achieves reversible response to ultraviolet and visible light and dynamic light emission switching, making it suitable for advanced information encryption and anti-counterfeiting materials.
Patent Information
- Application Number
- CN202510870872.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-11-21
AI Technical Summary
Existing dynamic optical encryption technology suffers from insufficient security, low reversibility, and poor multidimensional responsiveness. The processing performance and stability of traditional platinum (II) complexes and spiropyran molecules need to be improved in practical applications.
Using photochromic precursor materials Pt-AP and SP-AP, a core-shell structured organometallic silicon nanocomposite material Pt-SiO2@SP-SiO2 was prepared by combining it with the silica precursor TEOS through a heating reaction. This composite material was then doped into a polyurethane acrylate polymer matrix to prepare nanofiber films.
It achieves reversible response to ultraviolet and visible light, has time resolution and dual-wavelength dynamic light emission switching function, overcomes the limitations of traditional optical encryption materials, and is suitable for high-security anti-counterfeiting and flexible encryption devices.
Smart Images

Figure CN120987998A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of advanced functional materials and optical encryption technology, and particularly relates to a photochromic core-shell structure organometallic silicon nanocomposite material and a preparation and application thereof. BACKGROUND
[0002] Dynamic optical encryption technology as an important branch of modern information security field has been widely concerned in recent years. However, with the development of technology and the continuous improvement of application requirements, the demand for existing dynamic optical encryption technology gradually shifts to enhanced security, improved reversibility and multi-dimensional responsiveness. Traditional systems relying on static light-emitting labels or single-color switching characteristics have serious limitations, including simple encryption logic, easy copying and susceptibility to environmental interference.
[0003] Platinum (II) complexes have broad application prospects as optical materials due to their adjustable emission wavelength, long phosphorescence lifetime, strong processability and high quantum yield. However, in practical applications, they have single light-emitting color encryption logic, and their processability and stability still need to be improved. Similarly, spiropyrans (SP) as a classic photochromic molecule can be reversibly converted between the non-conjugated colorless SP configuration and the conjugated colored merocyanine (MC) configuration driven by ultraviolet / visible light. However, their photochromic performance also faces some challenges in practical applications, such as low isomerization freedom in solid material devices, resulting in low photochromic efficiency, and insufficient stability in complex chemical environments.
[0004] Therefore, in order to overcome the shortcomings of existing dynamic optical encryption technology and meet the demand for enhanced security, improved reversibility and multi-dimensional responsiveness, it is urgent to develop a new type of organometallic silicon nanocomposite material. SUMMARY
[0005] The first object of the present application is to provide a photochromic precursor material to overcome the shortcomings of the prior art.
[0006] To achieve the above object, the following technical solutions are adopted in the present application: A photochromic precursor material, whose molecular formula is as shown in the following formula Pt-AP and SP-AP: Molecular formula Pt-AP and SP-AP Pt-AP exhibits green phosphorescence, and SP-AP can be reversibly converted in optical properties by ultraviolet / visible light.
[0007] The second object of the present application is to provide a method for preparing a photochromic core-shell structure organometallic silicon nanocomposite material using the above-mentioned precursor material, which comprises the following steps: Step (1), under heating condition, react platinum (II) complex precursor with (3-aminopropyl) triethoxysilane in chloroform solvent to obtain Pt-AP; Step (2), under heating condition, react carboxyl-containing spiropyran (SP-COOH) with (3-aminopropyl) triethoxysilane in mixed organic solvent, and add catalyst to obtain SP-AP. Step (3), under room temperature condition, add Pt-AP to basic solution of ethanol and water with tetraethoxysilane (TEOS) as silica precursor to obtain core silica nanoparticle Pt-SiO2. Step (4), resuspend core silica nanoparticle Pt-SiO2, then add surfactant, SP-AP and tetraethoxysilane (TEOS) to obtain the photochromic core-shell structure organic metal silicon nanocomposite Pt-SiO2@SP-SiO2.
[0008] Further, the molar ratio of Pt-AP to SP-AP is 1:1-7.
[0009] Further, the mixed organic solvent in step (2) is a mixed solvent of chloroform and N,N-dimethylformamide (DMF).
[0010] Further, the catalyst in step (2) is a combination of EDC·HCl and 4-dimethylaminopyridine (DMAP).
[0011] Further, the surfactant in step (4) is cetyltrimethylammonium bromide (CTAB).
[0012] The third object of the present application is to provide a photochromic core-shell structure organic metal silicon nanocomposite prepared by the above method.
[0013] The fourth object of the present application is to provide the application of the above photochromic core-shell structure organic metal silicon nanocomposite as patterning material.
[0014] Further, the application is specifically: by electrospinning process, the composite material is doped in polyurethane acrylate (PUA) high molecular matrix to prepare large-area processable nanofiber film.
[0015] The fifth object of the present application is to provide the application of the above photochromic core-shell structure organic metal silicon nanocomposite as anti-counterfeiting material.
[0016] The sixth object of the present application is to provide the application of the photochromic core-shell structure organometallic silicon nanocomposite in the preparation of flexible encryption devices.
[0017] Compared with the prior art, the present application has the following beneficial effects: The present application has the advantages of simple preparation process, easy purification, reversible response to ultraviolet light and visible light, time resolution, and dual-wavelength dynamic light switching function of the obtained photochromic composite material and nanofiber film.
[0018] The composite material has reversible response to ultraviolet light and visible light, can realize dynamic light switching under different wavelengths, and provides a new way for high-level information encryption and anti-counterfeiting, and is suitable for high-security anti-counterfeiting, information storage and flexible encryption devices. BRIEF DESCRIPTION OF DRAWINGS
[0019] In order to further illustrate the features and technical contents of the present application, please refer to the following drawings related to the present application, but the drawings are only for reference and illustration, and are not used to limit the present application.
[0020] Figure 1 is the nuclear magnetic hydrogen spectrum of the platinum (II) complex Pt-AP in deuterated chloroform; Figure 2 is the nuclear magnetic hydrogen spectrum of the spiropyran derivative SP-AP in deuterated chloroform; Figure 3 is the ultraviolet spectrum of Pt-AP in a dilute solution of DCM; Figure 4 is the emission spectrum of Pt-AP in a dilute solution of DCM; Figure 5 is the Fourier transform infrared spectrum of the compound and the composite material; Figure 6 is the comparison of the Fourier transform infrared spectra of the composite material Pt-SiO2@SP5-SiO2 before and after ultraviolet light irradiation; Figure 7 is the X-ray diffraction spectrum of the composite material; Figure 8 is the scanning electron microscope photograph of the composite material Pt-SiO2@SP5-SiO2; Figure 9 is the transmission electron microscope photograph of the composite material Pt-SiO2@SP5-SiO2; Figure 10 is the particle size distribution graph of the composite material Pt-SiO2@SP5-SiO2; Figure 11 is the UV spectrum change of the composite material Pt-SiO2@SP-SiO2 under continuous ultraviolet light; Figure 12 is the emission spectrum change of the composite material Pt-SiO2@SP-SiO2 under continuous ultraviolet light; Figure 13 is a scanning electron microscope photo of the nanofiber film; Figure 14 is the UV spectrum change of the nanofiber film under continuous ultraviolet light; Figure 15 is the emission spectrum change of the nanofiber film under continuous ultraviolet light; Figure 16 is an application schematic diagram of the nanofiber film as an advanced anti-counterfeiting and information storage material. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the present application clearer, the following will further describe the present application in combination with the drawings and examples. It should be noted that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application. In addition, the technical features involved in each embodiment of the present application described below can be combined with each other as long as they do not conflict with each other.
[0022] Example 1, synthesis of platinum (II) complex and spiropyran derivative: (1) Synthesis of platinum (II) complex Pt-AP: The CHCl3 solution (60.0 mL) of the platinum (II) complex precursor (1.06 g, 1.86 mmol) was mixed with (3-aminopropyl) triethoxysilane (AP, 1.24 g, 5.58 mmol). The mixture was refluxed and stirred for 48 hours. After cooling to room temperature, the solvent was removed under reduced pressure, and the crude product was purified by dichloromethane (DCM) and ethyl acetate (EA) column chromatography (DCM:EA = 30:1, v / v) to obtain light green crystals (1.05 g) with a yield of 70.0%. 1 H NMR (500 MHz, CDCl3) delta 9.43 (t, J = 3.0 Hz,1H), 8.49 (s, 1H), 7.90 (m, J = 8.6, 5.1, 2.9 Hz, 1H), 7.45 (m, J= 9.6, 6.9, 2.9Hz, 1H), 7.21 (s, 1H), 7.16 (dd, J = 7.0, 2.2 Hz, 1H), 6.86 (dd, J = 8.9, 2.4 Hz, 1H), 6.52 (m, J = 12.6, 8.8, 2.4 Hz, 1H), 6.01 (t, J = 6.0 Hz, 1H), 3.89 (dd, J =13.5, 6.8 Hz, 1H), 3.72–3.63 (m, 6H), 3.64–3.48 (m, 2H), 2.51 (s, 3H), 2.41(s, 3H), 1.64 (m, J = 13.7, 7.9 Hz, 2H), 1.09 (t, J = 7.0 Hz, 9H), 0.52–0.44 (m, 2H). See NMR spectrum. Figure 1 .
[0023] (2) Synthesis of the spiropyran derivative SP-AP: Carboxyspiropyran (SP-COOH, 0.50 g, 1.31 mmol) and AP (0.35 g, 1.58 mmol) were dissolved in a mixed solvent of chloroform (80.0 mL) and DMF (7.0 mL), and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC·HCl, 0.37 g, 1.93 mmol) and 4-dimethylaminopyridine (DMAP, 16.0 mg, 0.13 mmol) were added. The mixture was stirred overnight at 62 °C. After the reaction was complete, the solvent was removed under reduced pressure, and the crude product was purified by DCM and EA (DCM:EA = 4:1, v / v) column chromatography to give a purple powder (0.51 g), with a yield of 67.0%. 1 H NMR (500 MHz, CDCl3) delta 8.09–7.93 (m, 2H), 7.19 (m, J = 7.6, 1.3 Hz, 1H), 7.08 (dd, J = 7.3, 1.2 Hz, 1H), 6.95–6.85 (m, 2H), 6.72 (d, J = 8.6 Hz, 1H), 6.64 (d, J= 7.7 Hz, 1H), 5.83 (d, J =10.4 Hz, 1H), 5.68 (d, J = 6.5 Hz, 1H), 3.78 (q, J = 7.0 Hz, 6H), 3.73–3.42 (m,2H), 3.17 (m, J = 15.1, 6.8 Hz, 2H), 2.55–2.33 (m, 2H), 1.55 (d, J = 10.2 Hz,2H), 1.26 (s, 6H), 1.20 (t, J = 7.0 Hz, 9H), 0.59–0.52 (m, 2H). See NMR spectrum. Figure 2 .
[0024] Example 2: Preparation method of core-shell structured organometallic silicon nanocomposite Pt-SiO2@SP-SiO2 Core silica nanoparticles were prepared in an alkaline solution using tetraethoxysilane (TEOS) as a silica precursor. Ethanol (50.0 mL), deionized water (4.0 mL), and concentrated ammonia solution (30%, 1.0 mL) were mixed. TEOS (3.0 mL) and Pt-AP (60.0 mg) were added to this mixture, and the mixture was reacted overnight at room temperature to obtain a Pt-SiO2 suspension. Surfactant CTAB (120.0 mg) was dissolved in a mixed solvent of deionized water (22.8 mL) and ethanol (9.6 mL). The Pt-SiO2 suspension (10.0 mL) was then added to the above solution, and the mixture was stirred at room temperature for 30 minutes. Subsequently, SP-AP (7.4 mg) and TEOS (0.2 mL) were added to the mixture, and the mixture was stirred overnight at room temperature. After the reaction was completed, the nanoparticles were collected by centrifugation and the solid was washed three times with ethanol to obtain the core-shell composite material Pt-SiO2@SP1-SiO2 (362.3 mg).
[0025] To investigate the effect of different energy donor-acceptor ratios on the optical properties of composite materials, the amount of SP-AP was adjusted to 22.0 mg, 37.0 mg, and 51.8 mg (the molar ratio of Pt-AP to SP-AP was 1:3, 1:5, and 1:7) according to the same procedure, resulting in Pt-SiO2@SP3-SiO2 (373.5 mg), Pt-SiO2@SP5-SiO2 (382.3 mg), and Pt-SiO2@SP7-SiO2 (391.8 mg), respectively.
[0026] Example 3: Preparation of photochromic nanofiber thin films The prepared composite material Pt-SiO2@SP5-SiO2 was dispersed in a 20% (w / w) DMF solution of PUA to obtain a spinning solution. A 10 mL syringe was used to draw the prepared spinning solution, which was then installed on an electrospinning machine. A positive high voltage was applied to the syringe equipped with a metal needle, and the syringe was propelled by a peristaltic pump. The spinning parameters are shown in Table 1. Tin foil was placed on a receiving device to collect the electrospun film composed of nanofibers. The resulting film exhibited photochromic properties.
[0027] Table 1: Specific spinning parameters Example 4: Structural characterization and optical property study of organometallic silicon nanocomposites and nanofiber membranes: The synthesized Pt-AP was dissolved in a dilute DCM solution, and the UV and emission spectra of Pt-AP in the dilute DCM solution were recorded using UV-Vis spectroscopy and fluorescence spectroscopy, respectively. The results are as follows: Figure 3 and Figure 4 As shown.
[0028] The infrared spectrum of SP-AP was recorded using a Fourier transform infrared spectrometer (FT-IR). Figure 5 The successful grafting of the compound was confirmed by characteristic absorption peaks. The composite material Pt-SiO2@SP5-SiO2 was subjected to FT-IR tests before and after UV irradiation, and its infrared spectra were recorded. Figure 6 The efficient isomerization of spiropyran was compared and analyzed. Fourier transform infrared spectroscopy confirmed the successful grafting of the two compounds and the efficient isomerization of spiropyran.
[0029] The Pt-SiO2@SP5-SiO2 composite material was tested using X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and dynamic light scattering (DLS). X-ray diffraction confirmed that the compound exists in an amorphous state within a silica framework (see [link to XRD]). Figure 7 The prepared composite material Pt-SiO2@SP5-SiO2 exhibits a distinct spherical core-shell structure and a particle diameter of approximately 233.12 nm (see...). Figure 8 , Figure 9 and Figure 10 ).
[0030] The composite material changes from light yellow to purple under UV light. With the increase of SP ratio, the characteristic absorption of MC at 560 nm increases, and the purple appearance is also deeper. For low SP content (Pt-SiO2@SP1- / SP3-SiO2), due to the limited MC acceptor, the energy transfer is limited, resulting in the intermediate color (yellow / orange) of the luminescence color; for high SP content (Pt-SiO2@SP5- / SP7-SiO2), the ideal donor-acceptor ratio promotes energy transfer, realizing red emission (see Figure 11 and Figure 12 ).
[0031] The morphology of the nanofiber film obtained in Example 3 was observed using a scanning electron microscope (SEM). Then, the nanofiber film was exposed to UV light, and the change in the UV spectrum of the nanofiber film under continuous UV light was recorded using a UV-visible spectrometer, and the change in the emission spectrum of the nanofiber film under continuous UV light was recorded using a fluorescence spectrometer. It can be seen that the nanofiber has a diameter of about 250.00 nm, and has a photochromic property similar to a solid (see Figure 13 , Figure 14 and Figure 15 ).
[0032] Application Example 1: Using the film of Example 3 as a patterning material The prepared film can be used as a patterning material for advanced information encryption and anti-counterfeiting. Information can be written into the film by mask method under UV light irradiation. After removing the mask, the information can be read by appearance and continuous UV light irradiation, realizing dynamic anti-counterfeiting authentication. After 60 seconds of UV light irradiation, the encrypted information can be eliminated, and the film can be restored to its original state by visible light irradiation for 3 minutes, for multiple cycles (see Figure 16 ).
[0033] The above-described embodiments are merely specific embodiments of the present application, which are used to illustrate the technical solutions of the present application, but not to limit the same. The protection scope of the present application is not limited thereto. Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can make modifications or easily think of changes to the technical solutions recorded in the foregoing embodiments, or make equivalent replacements to some of the technical features, without departing from the technical scope disclosed by the present application. Such modifications, changes or replacements do not cause the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present application, and should be covered within the protection scope of the present application.
Claims
1. A photochromic precursor material, characterized in that, Its molecular formulas are shown in the following formulas: Pt-AP and SP-AP:
2. A method for preparing photochromic core-shell structured organometallic silicon nanocomposite materials using the precursor material as described in claim 1, characterized in that, The method includes the following steps: Step (1): Under heating conditions, the platinum (II) complex precursor was reacted with (3-aminopropyl)triethoxysilane in chloroform solvent to obtain Pt-AP; Step (2): Under heating conditions, spiropyran containing carboxyl groups and (3-aminopropyl)triethoxysilane are placed in a mixed organic solvent, and a catalyst is added to react and obtain SP-AP; Step (3): At room temperature, using tetraethoxysilane as a silica precursor, Pt-AP is added to an alkaline solution of ethanol and water to react and obtain core silica nanoparticles Pt-SiO2. Step (4): The core silica nanoparticles Pt-SiO2 are resuspended, and then surfactant, SP-AP and tetraethoxysilane are added to react and obtain the photochromic core-shell structure organometallic silicon nanocomposite Pt-SiO2@SP-SiO2.
3. The method according to claim 2, characterized in that, The molar ratio of Pt-AP to SP-AP is 1:1-7.
4. The method according to claim 2, characterized in that, The mixed organic solvent in step (2) is a mixture of chloroform and N,N-dimethylformamide; the catalyst is a combination of EDC·HCl and 4-dimethylaminopyridine.
5. The method according to claim 2, characterized in that, The surfactant used in step (4) is hexadecyltrimethylammonium bromide.
6. A photochromic core-shell structured organometallic silicon nanocomposite material, characterized in that, It is prepared by the method described in any one of claims 2-5.
7. The application of the photochromic core-shell structured organometallic silicon nanocomposite material as described in claim 6 as a patterning material.
8. The application according to claim 7, characterized in that, The specific application is as follows: the composite material is doped into a polyurethane acrylate polymer matrix by electrospinning to prepare a nanofiber film.
9. The application of the photochromic core-shell structured organometallic silicon nanocomposite material as described in claim 6 as an anti-counterfeiting material.
10. The application of the photochromic core-shell structured organometallic silicon nanocomposite material as described in claim 6 in the fabrication of flexible encryption devices.